The Protective Effect of Jiaji Point Injection of Astragali on Gastric Mucosa in Rats with Bile Reflux Gastritis - 陈玉其 艾炳蔚 李玉堂 (Journal of acupuncture and tuina science, 2005)
To investigate the protective effect of Jiaji point injection of Huangqi (Radix Astragali) on gastric mucosa in rats with bile reflux gastritis (BRG). Methods: Jiaji (Ex-B 2) points lateral to below T9-12 spinal processes were injected with Huangqi (Radix Astragali) in rats with bile reflux gastritis to investigateits effecton gastric mucosa and gastrointestinal peptide hormone level.